Manifesto of the New Economy: Institutions and Business Models of the Digital Society - Dolgin, Alexander (Springer Nature, 2011)
Economic Theory/Quantitative Economics/Mathematical Methods; Methodology/History of Economic Thought; Business and Management, general; Computer Appl. in Social and Behavioral Sciences; Computer Communication Networks; Social Sciences, general